Social Perspective of Trafficked Survivor - Sapkota, Bishnu (Sotang, Yearly Peer Reviewed Journal, 2021)
Article explores about the condition and situation of human trafficking survivor. It is social problem all over world which includes exploitation of human trafficking. It describes about life circumstances and insight of society and community as well as it describes about different theoretical perspective, and wellbeing about the negligent of society. Despites are involved along with it. It includes about the condition of victims and their huge challenge during the COVID-19. It gives positive thinking and quality health service opportunity, education social justice, provides productive information and environment will minimize problem. A well being program should be organize for the victims of survivor in our society